Detecção molecular do complexo viral da murcha do abacaxizeiro em plantas e no inseto vetor - Amorim, Walkíria Andrade de (2011)
Brazil is one of the largest producers of pineapple, but the crop can have high economic losses due to diseases like mealybug wilt, caused by one or more Pineapple mealybug wilt-associated viruses (PMWaVs) with yield losses up to 80%. This study aimed to develop a methodology to detect the virus complex in plants and insect vectors, efficiently, simply and at low cost. Samples of plants and mealybugs were collected at the Experimental Farm of Incaper in Sooretama, at the Centro Serrano Regional Development Center in Domingos Martins, and at commercial plantations in the municipality of Marataízes, Espírito Santo, for virus detection by RT-PCR using degenerate primers. The results showed that the samples must be processed in the laboratory within 48 hours of collection or stored in a freezer for a maximum of 30 days. For samples of plants in vitro, and the green, pigmented leaf region and roots of plants from the field, the best protocol for RNA extraction was found to be Trizol®, and for chlorotic, unpigmented leaf tissues the method of Doyle and Doyle (1990) was preferable. In older leaves of plants from the field, we could not detect the virus. It was observed that absence of wilt symptoms in plants did not guarantee absence of the virus. In analysis of plants in tissue culture, we detected the presence of the virus in 15% of samples. The technique for viral diagnosis in mealybugs was standardized using degenerate and specific primers and Trizol® reagent, from the protocol of Gibbs and Mackenzie (1997). Although the mealybug Dysmicoccus brevipes is considered a vector, this is the first time that PMWaV has been detected in this insect by PCR with three PMWaVs detected in the same insect. The new methodology developed in this research was shown to be viable for the diagnosis of disease, disease indexing of propagative material, and detection of the virus in insect vector.